PERSONAL HYGIENE COUNSELING AS AN EFFORT TO PREVENT INFECTIOUS DISEASES IN ELEMENTARY SCHOOL CHILDREN IN KOTO MASJID VILLAGE - Salim, Agus; Neni Afriyani; Dian Fetri Harahap (Awal Bros Journal of Community Development, 2026)
ABSTRACT Koto Masjid Village is a village in Koto Kampar District XIII, with a fairly busy community. One important aspect of maintaining public health is instilling clean and healthy lifestyle habits from an early age in elementary school-aged children. In response to this situation, the author initiated the "Personal Hygiene Counseling as an Effort to Prevent Infectious Diseases in Elementary School Children in Koto Masjid Village" work program to increase awareness and encourage elementary school students to practice personal hygiene. This activity was implemented through an interactive counseling method that directly involved students. The main focus of the material covered crucial steps in maintaining personal hygiene, from proper handwashing with soap and coughing and sneezing etiquette to prevent the spread of germs, the importance of using personal eating utensils and toiletries (not sharing), to education about nail and skin hygiene. This education is crucial for providing a proper understanding of the prevention of infectious diseases that frequently occur in the school environment. As a means of ongoing education, the author also created and displayed guide posters at strategic points around the school. The poster provides a concise visualization of handwashing procedures, coughing and sneezing etiquette, personal hygiene, and nail and skin care. The expected outcome is increased health literacy and behavioral changes among students in Koto Masjid Village, resulting in a healthier school environment responsive to preventing disease transmission at the individual level.